Multiscale Model Identifies Improved Schedule for Treatment of Acute Myeloid Leukemia In Vitro With the Mcl‐1 Inhibitor AZD5991. (17th September 2020) - Goliaei, Ardeshir; Woods, Haley A.; Tron, Adriana E.; Belmonte, Matthew A.; Secrist, J. Paul; Ferguson, Douglas; Drew, Lisa; Fretland, Adrian J.; Aldridge, Bree B.; Gibbons, Francis D.
Abstract : Anticancer efficacy is driven not only by dose but also by frequency and duration of treatment. We describe a multiscale model combining cell cycle, cellular heterogeneity of B‐cell lymphoma 2 family proteins, and pharmacology of AZD5991, a potent small‐molecule inhibitor of myeloid cell leukemia 1 (Mcl‐1). The model was calibrated using in vitro viability data for the MV‐4‐11 acute myeloid leukemia cell line under continuous incubation for 72 hours at concentrations of 0.03–30 μM. Using a virtual screen, we identified two schedules as having significantly different predicted efficacy and showed experimentally that a "short" schedule (treating cells for 6 of 24 hours) is significantly better able to maintain the rate of cell kill during treatment than a "long" schedule (18 of 24 hours). This work suggests that resistance can be driven by heterogeneity in protein expression of Mcl‐1 alone without requiring mutation or resistant subclones and demonstrates the utility of mathematical models in efficiently identifying regimens for experimental exploration.